Grammar Translation Method's Effect on Yemeni Advanced Students' English Production in Communicative Situations - Ali Mohammed Saleh Al-Hamzi (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2020)
In the past and present, the Yemeni government provided free education at all levels of public education. Until the early days, and more precisely until now, the Yemeni government used to send honorary high school students to pursue their university studies abroad, honour university students to pursue a master's degree abroad, and honour holders of a master's degree abroad to pursue a doctorate study. They all obtain special certificates from Egypt, India, the United Kingdom, Australia, and other countries worldwide. EFL was learned at the seventh-grade level. While the Yemeni government has made all these attempts, English for the success of Yemeni advanced students' English production in communication contexts has been unsatisfactory. Several studies in the Arab world, particularly in Yemeni contexts, have shown that the main explanation for this discontent is the method used in Yemeni schools to teach English. Therefore, this research aims to find out the effect of this method on Yemeni students' performance in the English language when they speak English. This study follows a qualitative research method that focuses on secondary sources represented in literature reviews and primary resources expressed in interviews with ten Yemeni English teachers. The study reached many results, the most important of which is that GTM does not necessarily allow Yemeni students to use the English language communicatively. Instead, it allows them to learn about English as a subject. The study makes several suggestions on the basis of the study's findings. In particular, English language teachers should use other effective teaching approaches to help Yemeni students use the English language in communicative contexts, and grammar must be taught in context.